An all-dielectric route to negative refraction - Darshini AppandaI (Nanyang Technological University, 2022)
When light travels from one medium to another with a different refractive index, it will bend at the interface and this bending of light is called refraction. In the materials found in nature, the incident light beam and the refracted light beam lie in the opposite side of the normal to the surface. However, theoretical, and experimental developments show that, contrary to what we find in nature, the incident and refracted light beams can in fact lie on the same side of the surface normal. This phenomenon is called negative refraction and such artificially created metamaterials which facilitate negative refraction are known as ‘left-handed materials’ or ‘double negative (DNG) metamaterials. Most of these metamaterial designs have been metal based. They have large dissipation losses which greatly reduces the performance of the devices. In this project, a new approach by using all dielectric resonators to achieve low-loss negative refraction will be explored. We will be using the Wolfram Mathematica software to mathematically derive the effective electric permittivity and effective magnetic permeability. We will then be using COMSOL Multiphysics 5.5 software to model an array of dielectric resonators from the derived values. This will then be followed by the propagation of electromagnetic (EM) waves through the resonators to observe negative refraction.